Influence of surface-modified South African coal fly ash on the mechanical properties of cis-1 4-polyisoprene rubber vulcanizates - Van der Merwe, E.M. (Elizabet Margaretha) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.